Development of sensing and measurement system with input of acoustic signals - Wang, Jing Xuan (Nanyang Technological University, 2022)
The Unmanned Surface Vessels (USV) are used extensively for military and research purposes, which were developed to reduce the risks associated with underwater operations. Integrating the Underwater Acoustic System (UWAS) on USV can offer numerous advantages, such as providing comprehensive and precise data. However, the ability of a USV to successfully detect and acquire source information is highly dependent on the UWAS. Accordingly, there is a need for improved UWAS, and Graphical User Interface holds promise for this application.